Penyuluhan dan pelatihan membuat tempat cuci dapur dan drainase rumah panggung di Desa Salobukkang - Panennungi T.; Bakhrani A. Rauf (DEDIKASI, 2020)
This social work aimed to improve: (1) partner’s knowledge kitchen washing place and drainage (2) partner’s skill to kitchen washing place and drainage and (3) the skill to make kitchen washing place and drainage. The methods that used of this social work were : (1) to improve the knowledge of people about the kitchen washing place and drainage of stilt house then the discourse, interactive and discussion method are conducted, (2) to improve their skill to design the kitchen washing place and drainage then methods discourse, interactive, discussion, and demonstration are conducted and (3) to improve the skill to make the kitchen washing place and drainage then discourse, interactive, discussion, demonstration, and training methods are conducted. The results of social work, (1) the people was highly motivated to follow these activities; (2) the material of workshop was responded by people because of kitchen washing place and drainage of stilt house was easy to be made and the compound could be gained in workshop location; (3) kitchen washing place and drainage of stilt house could be accepted, understood, and followed by people technically; (4) the people were ready to make their own kitchen washing place and drainage construction in their house and inform to others.